Bio-Matched Antennas With Flare Extensions for Reduced Low Frequency Cutoff - John Blauert; Asimina Kiourti (IEEE Open Journal of Antennas and Propagation, 2020)
We recently reported a new class of broadband and high gain antennas for into-body radiation, called Bio-Matched Antennas (BMAs). A major limitation of our prior work is that BMA volume increases significantly as the low cutoff frequency is reduced. This is particularly troublesome for into-body applications where low operating frequencies are needed to penetrate deep into the tissues. Here, we overcome this challenge via a novel design that extends the BMA's conducting flares along the tissue surface. In doing so, the antenna's lowest operating frequency is reduced, while its volume remains unaltered. For an example BMA of 1161.3 mm3 in volume, our new approach results in lowering the cutoff frequency from 1.9 GHz to 830 MHz. Additional novelties brought forward include: (a) the first testing of BMAs through stratified tissue models (as opposed to homogeneous models explored in the past), and (b) the smallest volume BMA reported to date, which also exhibits the lowest frequency cutoff as well as comparable or better transmission loss vs. previous designs.